Pengaruh Disiplin Kerja, Beban Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan - Agri Ristya Bimantara; Epsilandri Septyarini; Eko Yulianto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to determine the influence of work discipline, workload, and work environment on employee performance at the Mranggen village office.The method used in this study is a quantitative approach. The population in this research consists of employees working at the Mranggen village office, with a sample of 40 respondents selected using Saturation Sampling  technique. The data analysis method used is multiple linear regression analysis.The results of the study show that, based on the t-test and F-test, work discipline and work environment have a positive and significant effect on employee performance. Meanwhile, workload has a negative and significant effect on employee performance. Furthermore, work discipline, workload, and work environment simultaneously have a significant effect on employee performance.This study supports various theories that highlight the significant role of work discipline and work environment in shaping employee performance. The implication of this research is expected to contribute to the improvement of employee performance.